2017
DOI: 10.1101/150516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic architecture of early childhood growth phenotypes gives insights into their link with later obesity

Abstract: Early childhood growth patterns are associated with adult metabolic health, but the underlying mechanisms are unclear.We performed genome-wide meta-analyses and follow-up in up to 22,769 European children for six early growth phenotypes derived from longitudinal data: peak height and weight velocities, age and body mass index (BMI) at adiposity peak (AP ~9 months) and rebound (AR ~5-6 years). We identified four associated loci (P< 5x10 -8 ): LEPR/LEPROT with BMI at AP, FTO and TFAP2B with Age at AR and GNPDA2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…In fact, they are not in LD with any marker associated with adult diseases, and might thus promote healthy weight gain during infancy, a notion further supported at the genome level by LD score regression. This result is further supported by a recent independent study 34 suggesting that SNPs in the LEPR/LEPROT locus are associated with BMI at the adiposity peak.…”
supporting
confidence: 83%
“…In fact, they are not in LD with any marker associated with adult diseases, and might thus promote healthy weight gain during infancy, a notion further supported at the genome level by LD score regression. This result is further supported by a recent independent study 34 suggesting that SNPs in the LEPR/LEPROT locus are associated with BMI at the adiposity peak.…”
supporting
confidence: 83%
“…We are planning to generalize our study to these new GRS definitions in the near future. Also, our GRS definition is mainly based on SNPs found associated with BMI in adults and could be extended to include genetic variants more specific to children, taking advantage on recent GWAS discoveries [33][34][35].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Some very rare mutations are responsible for severe obesity syndrome in humans, 24 and more frequent variants have been associated with BMI variability and obesity in children and adolescents 23,25 . However, the association between individual LEPR variants and the evolution of child BMI has been investigated in few studies and has been suggested to vary according to age 26,27 . We hypothesized that cord blood leptin level and carriage of the rare G allele of a common LEPR variant, the rs9436303 single‐nucleotide polymorphism (SNP), can affect, independently or in interaction, early postnatal growth and later adiposity trajectories.…”
Section: Introductionmentioning
confidence: 99%